Practice regarding care of endotracheal tube among nurses working in teaching hospital, Bharatpur - Adhikari, Kanchan Mijar; Subba, Hem Kumari (Journal of Chitwan Medical College, 2020)
Background:Endotracheal intubation is a most common procedure to maintain oxygenation and ventilation among the patients who admitted to critical care unit. So, meticulous care is necessary to maintain airway patency and prevent from complications. The objective of the study was to assess the practice regarding care of endotracheal tube among nurses working at teaching hospital, Bharatpur. Methods: A descriptive, cross- sectional study was conducted among 56 nurses working in critical care units of a teaching hospital, Chitwan. Sample was selected by using non probability, consecutive sampling technique. Data were collected through structured self-administered questionnaire to measure the socio-demographic and professional related information and observation checklist was used to measure the practice regarding care of endotracheal tube. Data were analyzed using descriptive and inferential statistics to find out the association between variables. Results: Majority (89.3%) of the nurses were above 20 years old, 71.4% of them were completed Proficiency Certificate Level, 60.7% had work experience of equal and less than one year in critical care unit and all of them participated in in-service education. Among 56 nurses, 57.1% had satisfactory level of practice regarding care of endotracheal tube. Nurses had highest mean practice score (79.55%) on suctioning and lowest score (19.22%) on cuff pressure management. Conclusions: It is concluded that nurses had marginally satisfactory level of practice regarding care of endotracheal tube. Hence, there is need to provide regular training for nurses regarding patient’s care with endotracheal tube.